ANALISIS PENERAPAN OUTSOURCING PADA BANK SULSELBAR CABANG SYARIAH MAKASSAR - Fadhillah S Ramadhani; Andi Mappatompo (COMPETITIVENESS, 2019)
This research aims to discuss the application of outsourcing Bank Sulselbar Makassar Sharia Branch. Using qualitative approach data collection through in-depth interviews with the number of informants 7 people.The results showed that the application of outsourcing is going well. This can be seen from the indicators used as a reference in the application of outsourcing. These indicators are outsourcing planning, strategy selection, cost analysis, employer selection, negotiation stage, resource transition and relationship management.  From these indicators in general it has been well applied. However, there are still some shortcomings in the application of outsourcing, namely from the provision of guarantees and payroll of outsourcing employees. The application of outsourcing is running well due to the supervision carried out by external parties and internal parties. Keywords: Human Resource Management, Outsourcing, and Outsourcing Implementation.